Preference for community health services in people with chronic diseases: a discrete choice experiment in China - Wang, Ke; Yang, Qian; Wan, Lei; An, Jingjing (Frontiers in Public Health, 2024)
BackgroundPrimary healthcare policies are widely implemented globally. However, many people with chronic diseases find that community-based chronic disease services do not meet their needs. There is a critical need for more evidence on the sustainability and optimization of chronic disease management in Chinese communities, especially from the demand side. Policymakers require detailed data on the needs of chronic disease patients regarding community health services.MethodsA discrete choice experiment was conducted to measure the preferences of people with chronic diseases. Researchers recruited participants in Sichuan Province, China, and conducted face-to-face surveys. The mixed logit model evaluated participants’ preferences for six attributes, estimating willingness to pay and relative importance, and performing subgroup analysis based on the initial model results.ResultsA total of 395 respondents participated in this study. Six attributes included all influenced the preference of people with chronic diseases for community health services. The most valued attribute for people with chronic diseases was drug accessibility (coefficient = 2.761, p < 0.001), followed by appointment referral (coefficient = 2.385, p < 0.001) and traditional Chinese medicine services (coefficient = 1.465, p < 0.001). The results were also borne out by the relative importance of attributes. Meanwhile, people with different types of chronic diseases were also most concerned about drug accessibility. There are differences in the willingness to pay for drug accessibility. Type II respondents had a higher WTP for services with high medicine accessibility (92.93 CNY) compared to Type I (67.05 CNY) and Type III (87.70 CNY) respondents.ConclusionThis study results highlight the importance of drug accessibility, appointment referral services, and traditional Chinese medicine services in community chronic disease management. These findings provide valuable insights for policymakers to optimize the current management of chronic diseases in Chinese communities.